2014
DOI: 10.7314/apjcp.2014.15.7.3201
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione S-Transferase T1 and M1 Polymorphisms and Risk of Uterine Cervical Lesions in Women from Central Serbia

Abstract: The aim of this study was to investigate the frequencies of GSTT1 and GSTM1 deletion polymorphisms in newly-diagnosed patients with uterine cervical lesions from central Serbia. Polymorphisms of GST genes were genotyped in 97 patients with cervical lesions and 50 healthy women using a multiplex polymerase chain reaction (PCR). The GSTM1 null genotype was significantly more prominent among the patients than in controls (74.2% vs 56.0%), the risk associated with lesions being almost 2.3-fold increased (OR=2.26, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 27 publications
1
12
1
1
Order By: Relevance
“…Contribution of the GSTM1-null to the development of various types of cancer has been documented with controversial conclusions (Duell et al, 2002;Roodi et al, 2004;Tiwawech et al, 2005;Liu et al, 2014;Stosic et al, 2014). Our present study identifying GSTM1 genotypes in the age matched case-control study could not find the effect of GSTM1 polymorphism on cervical carcinogenesis; the result rejects the association between genetic polymorphism of GSTM1 and increased risk for cervical cancer (Table 2).…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…Contribution of the GSTM1-null to the development of various types of cancer has been documented with controversial conclusions (Duell et al, 2002;Roodi et al, 2004;Tiwawech et al, 2005;Liu et al, 2014;Stosic et al, 2014). Our present study identifying GSTM1 genotypes in the age matched case-control study could not find the effect of GSTM1 polymorphism on cervical carcinogenesis; the result rejects the association between genetic polymorphism of GSTM1 and increased risk for cervical cancer (Table 2).…”
Section: Discussioncontrasting
confidence: 73%
“…This genotyping study confirmed our previous report on the GSTM1-null and cervical cancer (Settheetham-Ishida et al, 2009) and agreed with the previous finding in Caucasian (Chen et al, 1999), Japanese (Niwa et al, 2005), Indian ( Sobti et al, 2006, Singh et al, 2008, Sicilian (Agodi et al, 2010) and Italian ( Palma et al, 2010) women. In contrast, an association between the GSTM1 polymorphism and increased risk of cervical cancer was observed in central Serbia and suggested a possible important role of the GSTM1 deletion in the development of early stage of precancerous lesions (Stosic et al, 2014). Furthermore, a meta-analysis found GSTM1-null genotype showed an increased risk of uterine cervical lesions in Chinese and Indian but no risk for Japanese, European and American (Gao et al, 2011;Zhang et al, 2012).…”
Section: Discussionmentioning
confidence: 93%
“…21 studies of GSTM1 polymorphisms (2,250 CC cases and 3,025 controls) [6,8,[10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] , 17 studies of GSTT1 polymorphisms (1,704 CC cases and 2,060 controls) genotypes [6, 11-13, 15-17, 20-24, 26-30] , and 9 studies of GSTM1-GSTT1 interaction analyses (1,046 CC cases and 1,319 controls) [6,11,12,15,16,24,26,28] were included in our meta-analysis. The characteristics of the studies are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Studies performed in different countries such as India (Joseph et al, 2006), Italy (Palma et al, 2010) and Kasakhstan (Djangusurova et al, 2013), considered the GSTM1 and GSTT1 null polymorphism as a risk factor for cervical cancer. On the other hand, studies in countries such as Thailand (Ishida et al, 2009), Turkey (Kiran et al, 2010) and Serbia (Stosic et al, 2014), did not consider GSTM1 and GSTT1 null polymorphism as a risk factor for cervical cancer. In a study in Colombia (Sierra-Torres et al, 2006), the GSTM1 and GSTT1 null polymorphisms did not affect the risk for high grade intraepithelial lesions, suggesting other factors as more important for cancer evolution, such as high grade infection by HPV, exposition to mutagenic compounds and polymorphisms in other metabolism genes, such as CYP2E1.…”
Section: Discussionmentioning
confidence: 99%